Impact of COVID-19 pandemic on influenza vaccination rate among health care workers - Salah Alshagrawi (Taylor & Francis Group, 2024)
Vaccinations against influenza are critical in mitigating the severity of the disease, preventing its transmission, and restricting its dissemination. Concerns about vaccination hesitancy among healthcare workers (HCWs) have been duly recognized during and following the COVID-19 pandemic. To examine the extent to which the COVID-19 pandemic has influenced the adoption of vaccinations among HCWs. A cross-sectional online survey was conducted four years after the COVID-19 pandemic among HCWs in Saudi Arabia. We performed a logistic regression analysis using influenza vaccination uptake as the dependent variable and perceived COVID-19 pandemic's impact, age, gender, marital status, employment status, education level, monthly income, respondent's overall health, doctor visits, tobacco use, number of adults in the household, and number of children in the household as independent variables. The study included 574 participants, an 86% response rate. Of the sample, 47% reported they had the influenza vaccination. HCWs who reported a greater negative impact due to the COVID-19 pandemic were 40% more likely to acquire the influenza vaccine (OR = 1.4, 95% CI [1.24, 1.58]). Compared to HCWs without children, HCWs with a child had a 44% lower likelihood of taking the influenza vaccination (OR = 0.34, 95% CI [0.16, 0.69]). The odds of HCWs obtaining the influenza vaccine were 4.5 times higher for those who reported one yearly medical visit, 2.6 times higher for two, and 1.4 times higher for three or more. HCWs who experienced more severe COVID-19 outcomes were more likely to get vaccinated against the virus. However, long-term monitoring of this inclination is necessary.